Seeing ghosts: The absented presence of black lesbian women in mid-2000s Kwa-Thema and the legacies of trauma - Mabogwane, Kamohelo Bohlale (Department of English Language and Literature, 2023)
This project is about connections. Connections made from the body, from the personal, and from the spiritual. Putting into practice the concepts of autoethnography and affective research as methodologies that are lived, I use my body as an archive of experiences and geographic knowledges. In this approach, my personal subjective nature is not only recognised but also essential to the study of my own trauma as a living black lesbian woman and the vicarious trauma I experience in relation to the long list of assaulted and murdered black lesbian women in South Africa: specifically, the ones from my hometown of Kwa-Thema, Springs, in the mid-2000s, as well as the trauma of the black lesbian women I study in Jabulile Bongiwe Ngwenya's “I Ain't Yo Bitch” and Koleka Putuma's No Easter Sunday for Queers (in poem and play form). By analysing key moments in Zanele Muholi's documentaries Difficult Love and the Human Rights Watch's Zanele Muholi, Visual Activist, I foreground the “unbearable wrongness of being” and separation from citizenship and Africanness that black lesbians have experienced and continue to experience in this country.2 It is my position that the purpose of trauma is to ask questions about the past and the present. The absenting of black lesbian womanhood in the mid-2000s in Kwa-Thema was a massacre that shifted the social spatiality of the township from a queer haven for people in Johannesburg to a graveyard. Prioritising memory work through the Sojan trialectic of historicality, spatiality, and sociality, the Wynterian-McKittrickean demonic and geographic knowledges, and Gordonic hauntology leads me to the potential answers: what the process of seeing and witnessing allows as a Thirdspace for the hope of arriving at joy. This project is an exploration of what is absent and absented yet simultaneously present, and how it exists as such.